Analisis Spasial Temporal Penggunaan Lahan Kecamatan Moramo Dan Kecamatan Moramo Utara - Efraim Tandi Bua; La Ode Restele; Nurgiantoro Nurgiantoro; Saban Rahim; Fitriani Fitriani (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
Moramo and North Moramo Districts in South Konawe Regency have undergone temporal shifts in land use. This study aims to examine land use in these districts and discern changes in land area during 2007-2014, 2014-2022, and 2007-2022. Data sources encompass South Konawe Regency's spatial data, 2010, 2014, and 2022 data from the Central Statistics Bureau, Landsat 7, 8, and 9 satellite imagery, and RBI maps. Employing Supervised Classification and overlay methods, data were analyzed. In Moramo District, changes from 2007 to 2022 reveal increased built-up areas 420,41 acre, mixed gardens 95,46 acre, open lands 71,51 acre, mining 71,76 acre, and shrublands 37,19 acre, while paddy fields 104.89 acre, vegetation 507, 80 acre, water bodies 10,98 acre, and fishponds 72, 66 decreased. North Moramo District experienced augmented built-up areas 270,50 acre, open lands 8,79 acre, mining 352,89 acre, shrublands 17,37 acre, and water bodies 10,11 acre during 2007-2022. Conversely, paddy fields 0,25 acre, mixed gardens 251,09 acre, vegetation 356,55 acre, and fishponds 51,77 acre declined.